Palm Oil Leasing Practice Toward The Western-Southern Community of Aceh, Indonesia - Kurlillah, Anis; Al Bakri, Mirdat; Iskandar; Munadiati; Afna, Mauloeddin (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
The article overviewed the practice of leasing palm oil tree transactions which is popular in the western-southern of Aceh community. The practice of the transaction involved the beneficiaries, the owner, and the lessee, for the commodities as the commercial object. The study investigated the mechanism of leasing practice with an Ijarah of economic sharia. The study employed a qualitative method to deliver primary data which was acquired through informants’ interviews, and secondary supporting data from a literature review of books, journals, and research reports. The study result provided the lease transactions which were formerly expected to be worth economically. However, the transactions were considerably opposed to the practice of Ijarah, where there is the existence of the Gharar (Speculative) factor and violated the pillars of goods beneficial for mutual profit in the concept of its Sharia regulation. The violations were acclimatized for the unfulfillment of pillars and legal conditions for aqad for its lease practices.